Proceedings of the 4th International Conference on Contemporary Education, Social Sciences and Humanities (ICCESSH 2019) 2019
DOI: 10.2991/iccessh-19.2019.170
|View full text |Cite
|
Sign up to set email alerts
|

Study on Cultivating Students’ Critical Thinking Ability Through Higher Order Questioning

Abstract: In the contexts of unusually intense competition for international talents, no one denies the importance of cultivating students' critical thinking ability. Teaching students to think critically and creatively, however, is a great challenge to every classroom teacher. This article examines the role of teacher questions, discusses the connotation of higher order questions and classifications of questions-Bloom's Taxonomy of questions, Socratic questions and metacognitive questions, explores the relationship bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…All in all, what promotes thinking is good questions not correct answers, and the foremost successful strategy to think is to address questions which motivates individual thinking (Feng & Wei, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…All in all, what promotes thinking is good questions not correct answers, and the foremost successful strategy to think is to address questions which motivates individual thinking (Feng & Wei, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Constructing essay questions requires the mastery of teaching materials, skills in writing questions, and teachers' creativity in choosing the stimulus questions according to the situation and conditions of the school environment. Regarding the above findings, the results of research by Feng and Wei (2019) revealed that the questions that lead to higher-order thinking skills will encourage students to solve complex problems so that they can improve and develop critical thinking skills and ability to create innovation. Thus, when preparing questions for writing scientific texts, the teachers determine the behavior to be measured and formulate the material that will be used as the basis for the question (stimulus) in accordance with the expected behavior of the students.…”
Section: Writing the Grid And Criteria Of Critical Thinking Test Itemsmentioning
confidence: 92%